Analysis method based on coupled heat transfer and CFD simulations for buildings with thermally complex building envelopes. (15th March 2021) - Yamamoto, Tatsuhiro; Ozaki, Akihito; Kaoru, Suehiro; Taniguchi, Kazuhiro
Abstract: A thermal environment simulation method was developed for a structure with a thermally complex building envelope. The method used a heat transfer simulation (HTS), computational fluid dynamics (CFD), and a two-dimensional heat-flow calculation tool called Hygrabe2D. The general HTS does not support the modeling of buildings with a radial shape. Therefore, the building envelope was evaluated using a two-dimensional heat-flow computation tool coupled to the HTS. In the HTS, the amount of advection between zones for buildings with volumes that should be divided into multiple zones was unknown. The indoor surface temperature calculated by Hygrabe2D was coupled to the HTS, and the advection and convective heat transfer coefficients between zones were calculated via CFD, which were passed to the HTS. The accuracy of the proposed method was verified and validated. The influence of calculation accuracy was investigated by comparing the accuracies in the presence and absence of the coupling of the convective heat transfer coefficient. The initial conditional dependence of coupled advection between zones was confirmed, although it had no significant effect on the calculation accuracy. Through verification of the computational load reduction, we achieved computational accuracy with a small number of couplings. The proposed method was used to evaluate the thermal environment of a building by calculating the annual room temperature and temperature inside the building skin. Highlights: Hygrabe2D–THERB–CFD model analyzed the thermal environment of curved buildings. Thermal balance was achieved via THERB and CFD. A small number of couplings was enough to achieve high accuracy. Year-round thermal environment analysis reveals the thermostability of buildings.